Cultural infrastructure and regional economic well-being in Germany: Are we creative yet? - Thomas Krauskopf; Björn Bünger; Martin Langen (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
The influence of the creative class on regional economic well-being is discussed by using the concepts of Richard Florida. We apply this theory on the level of all German major cities in a 10 year period from 1997 to 2006. The theoretical part gives an overview about similar applications. The empirical part firstly describes the development of the theatre, employment and population structures of these cities. Secondly, these data are used to investigate a possible connection between theatre variables and economic growth (approximated by the municipal net tax base). We apply a balanced panel estimation with cross-section fixed effects on the data. It is shown that there is a connection between the growth of the number of theatre actors (proxy for the dimension of the creative class) and the growth of the net tax base. The growth of the number of actors Granger causes the growth of the net tax base. This result supports Florida's theory that the dimension of the creative class influences the economic well-being of a region.
Keywords: C33; R11; J24; 330; creative class; regional economic well-being; fixed effects estimation